2009
DOI: 10.1007/s11999-009-0899-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Alginate is a Carrier of OP-1 for Bone Induction

Abstract: Bone morphogenetic proteins (BMPs) can induce bone formation in vivo when combined with appropriate carriers. Several materials, including animal collagens and synthetic polymers, have been evaluated as carriers for BMPs. We examined alginate, an approved biomaterial for human use, as a carrier for BMP-7. In a mouse model of ectopic bone formation, the following four carriers for recombinant human OP-1 (BMP-7) were tested: alginate crosslinked by divalent cations (DC alginate), alginate crosslinked by covalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Although gingival connective tissue proliferates and/or attaches to the root surface, osteogenic modification of the root may initially acquire new and well‐established attachment to gingival connective tissue, and consequently inhibition of epithelial downgrowth may be elevated. BMPs have the ability to transform pluripotent stem cells into osteoprogenitor cells (9) and induce ectopic osteogenesis (10,11). Zaman et al.…”
mentioning
confidence: 99%
“…Although gingival connective tissue proliferates and/or attaches to the root surface, osteogenic modification of the root may initially acquire new and well‐established attachment to gingival connective tissue, and consequently inhibition of epithelial downgrowth may be elevated. BMPs have the ability to transform pluripotent stem cells into osteoprogenitor cells (9) and induce ectopic osteogenesis (10,11). Zaman et al.…”
mentioning
confidence: 99%
“…12 Therefore, an effective carrier must be used to achieve a localized effect at the desired bone healing site. BMP carriers can be classified as naturally occurring polymers, 13,14 synthetic polymers, 15 composites of synthetic and naturally occurring polymers, 8 and inorganic salts. 16 Bovine bonederived type I collagen is used as a carrier to bind rhBMP-7 in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, several strategies were developed to lower the dose of BMPs, which may decrease the dose-related complications, but achieve similar or more efficacious healing. These strategies include the use of delivery devices that allow better application of rhBMP-7 and obtain better retention at the surgery site, 7 the use of carriers that control the release of rhBMP-7, 8 and the use of a specific binding peptide that enhances the effect of rhBMP-2 in bone healing. 9 BMP binding peptide (BBP) was developed by Behnam et al 10 They isolated an 18.5 kDa fragment of the human bone matrix protein that has the chemical and physical properties of Urist's ''BMP.''…”
mentioning
confidence: 99%
“…13,14 They may induce mesenchymal stem cells to differentiate into osteoblasts, consequently resulting in bone formation on an ectopical site. [15][16][17] Our previous studies showed that a large recombinant human bone morphogenetic protein-7 (rhBMP-7)-loaded natural bovine bone mineral (NBBM) scaffold, once having been placed in the muscles of a miniature pig, was ossified and vascularized after 12 weeks. 10,[18][19][20] In the same way, we successfully cultivated a vascularized bone graft with custom shape in the latissimus dorsi muscle in a patient of subtotal mandible defect, which was caused by tumor resection.…”
Section: Introductionmentioning
confidence: 99%